A Discourse of Mabims New Criteria: Reading Difference Frequency Between Wujud al-Hilal and Imkan ar-Rukyat - Shofwatul Aini (Justicia Islamica, 2022)
In determining the beginning of the month of the Hijri calendar, the Indonesian government has used the criterion of crescent visibility (Imkan ar-Rukyat) adopted from the MABIMS agreement. This criterion has three conditions. Namely, the crescent should be at least at 20; the elongation is minimum at 30; the age of the crescent must be more than eight hours after conjunction. In August 2016, MABIMS made a great deal to revise this criterion. The new criterion has two conditions. Namely, the crescent should be at least 30, and the elongation is minimum at 6,40. This new criterion is planned to apply in Indonesia for the next few years and is wished to be accepted by all communities. The emergence of this new criterion leads to two main questions. First, how many frequencies of differences between this new criterion compared to the Wujud al-Hilal criterion, and the second is how if this new criterion is applied in Indonesia. This research used the elevation of the crescent to determine the frequency of differences between the new criterion compared to the Wujud al-Hilal criterion. It then analyzed it based on the former and the new criterion of the Imkan ar-Rukyat and the Wujud al-Hilal. The result shows significant differences between the new and Wujud al-Hilal criterion. If this new criterion is used in Indonesia, the togetherness of the beginning of the month of the Hijri calendar will decrease. Dalam menentukan awal bulan hijriyah, pemerintah Indonesia telah lama menggunakan kriteria Imkan ar-Rukyat yang diadopsi dari MABIMS yaitu syarat minimal tinggi hilal 20, sudut elongasi minimal 30, dan umur hilal minimal 8 jam setelah ijtimak. Pada bulan Agustus 2016 MABIMS telah menyepakati kriteria tersebut untuk direvisi dengan kriteria yang baru yaitu syarat awal bulan adalah tinggi hilal minimal 30, dan elongasi minimal 6,40. Kriteria yang baru ini rencananya akan diberlakukan di Indonesia dan diharapkan dapat diterima oleh semua pihak. Dengan adanya kriteria baru ini, ada dua rumusan masalah yang ingin diteliti lebih lanjut yaitu yang pertama adalah bagaimana frekuensi perbedaan kriteria baru ini dengan kriteria Wujud al-Hilal, dan yang kedua adalah bagaimana kriteria baru ini jika diterapkan di Indonesia. Untuk mengetahui frekuensi perbedaan kriteria baru ini dengan kriteria Wujud al-Hilal, penelitian ini menganalisisnya berdasarkan data timggi hilal dengan menggunakan acuan tiga kriteria yaitu Wujud al-Hilal, Imkan ar-Rukyat MABIMS yang lama, dan Imkan ar-Rukyat MABIMS yang baru. Dari hasil penelitian menunjukkan bahwa frekuensi perbedaan kriteria Imkan ar-Rukyat yang baru dengan kriteria Wujud al-Hilal semakin banyak. Selanjutnya jika kriteria Imkan ar-Rukyat MABIMS yang baru ini diterapkan di Indonesia, maka potensi kebersamaan dalam awal bulan hijriyah di Indonesia akan semakin berkurang.